2019
DOI: 10.1519/jsc.0000000000003063
|View full text |Cite
|
Sign up to set email alerts
|

Echo Intensity Reliability for the Analysis of Different Muscle Areas in Athletes

Abstract: Lanferdini, FJ, Manganelli, BF, Lopez, P, Klein, KD, Cadore, EL, and Vaz, MA. Echo intensity reliability for the analysis of different muscle areas in athletes. J Strength Cond Res 33(12): 3353–3360, 2019—Skeletal muscles' echo intensity (EI) is used as a parameter to evaluate muscle damage and muscle quality after exercise or training. However, recent muscle EI studies have used regions of interest (ROIs) of different sizes for assessing muscle damage and muscle quality, which may lead to different results if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Results of reliability of EI (r=0.75) and MT (r=0.99) demonstrated good-excellent values, which agrees with previous studies that evaluated the reliability of the measurements obtained by the US (LANFERDINI et al 2019;LIN et al 2015;PALMER et al 2015;RUAS et al 2017 1). Therefore, we propose that the MQ data could be corrected using Equation 1proposed by the present study, although the Bland-Altman test does not show any differences between EI and MQ measurements.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results of reliability of EI (r=0.75) and MT (r=0.99) demonstrated good-excellent values, which agrees with previous studies that evaluated the reliability of the measurements obtained by the US (LANFERDINI et al 2019;LIN et al 2015;PALMER et al 2015;RUAS et al 2017 1). Therefore, we propose that the MQ data could be corrected using Equation 1proposed by the present study, although the Bland-Altman test does not show any differences between EI and MQ measurements.…”
Section: Discussionsupporting
confidence: 89%
“…US is commonly used for muscle thickness (MT) measurement (BJORNSEN et al 2016;DE BOER et al 2008;LI et al 2013;REEVES et al 2009). However, the US has also been used to quantify echo intensity (EI), which reflects muscle quality (LANFERDINI et al 2019;PALMER et al 2015;RUAS et al 2017; SANTOS; ARMADA-DA-SILVA, 2017). The infiltration of fat and fibrous tissues increases the Brazilian Journal of Development, Curitiba, v.7, n.4, p. 33910-33923apr 2021 number of echoes or reflections from the ultrasound within the muscle, which is directly correlated with increases in EI and, consequently, worsening muscle quality (WATANABE et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The present study also examined larger ROIs within the image of the VL than Caresio et al. (25) did in the tibialis anterior, and EI reliability improves when larger regions are examined (25,41). Notably, the values for EI DEEP were less than EI FULL , and both were less than EI SUPF in our study, whereas Caresio et al.…”
Section: Discussionmentioning
confidence: 58%
“…Different muscle fiber arrangements between the VL (unipennate muscle) and the tibialis anterior (circumpennate muscle) may explain these opposing results, as EI heterogeneity within an individual image may be influenced by muscle architecture, independent of muscle depth (25,27). The present study also examined larger ROIs within the image of the VL than Caresio et al (25) did in the tibialis anterior, and EI reliability improves when larger regions are examined (25,41). Notably, the values for EI DEEP were less than EI FULL , and both were less than EI SUPF in our study, whereas Caresio et al reported lower EI of both the superficial and deep portions than EI of the full muscle, indicating that regions of the muscle with higher EI were not included in either the superficial or deep regions selected by Caresio et al (25).…”
Section: Ultrasound Assessmentsmentioning
confidence: 60%
“…Low echo intensity values are considered to be associated with greater muscle quality; in contrast, high echo intensity values are thought to be related to muscle impairment [33]. US has been shown to be a reliable tool for the assessment of muscle quality as echo intensity in different populations [33], including young athletes [36]. Echo intensity has been mainly used to study muscle quality changes in aging [34], although attempts to apply it in a sports setting have been conducted [37][38][39].…”
Section: Muscle Qualitymentioning
confidence: 99%